"Dude, You're Such a Slut!" Barriers and Facilitators of Sexual Communication Among Young Gay Men and Their Best Friends. (July 2014) - McDavitt, Bryce; Mutchler, Matt G.
Conversations with friends are a crucial source of information about sexuality for young gay men, and a key way that sexual health norms are shared during emerging adulthood. However, friends can only provide this support if they are able to talk openly about sexuality. We explored this issue through qualitative interviews with an ethnically diverse sample of young gay men and their best friends. Using theories of sexual scripts, stigma, and emerging adulthood, we examined how conversations about sex could be obstructed or facilitated by several key factors, including judgmentalism, comfort/discomfort, and receptivity. Gay male friends sometimes spoke about unprotected sex in judgmental ways (e.g., calling a friend "slut" or "whore" for having sex without condoms). In some cases, this language could be used playfully, while in others it had the effect of shaming a friend and obstructing further communication about sexual risk. Female friends were rarely openly judgmental, but often felt uncomfortable talking about gay male sexuality, which could render this topic taboo. Sexual communication was facilitated most effectively when friends encouraged it through humor or supportive questioning. Drawing on these findings, we show how judgmentalism and discomfort may generate sexual scripts with contradictory norms, and potentially obstruct support from friends around sexual exploration during a period of life when it may be most developmentally important.